Pengaruh Stres Kerja Dan Beban Kerja Terhadap Turnover Intention Pada PT. JNE Padang - Nadia Zafriarni; Mellyna Eka Yan Fitri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study is a survey research conducted on employees of PT. JNE Padang. The study is titled "The Effect of Work Stress and Workload on Turnover Intention at PT. JNE Padang." The purpose of this study is to determine the effect of work stress and workload on turnover intention. This research is quantitative, and the data collection methods include surveys, questionnaires, and interviews. The population in this study consists of all employees of PT. JNE Padang, totaling 229 individuals. The sample size for this study is 127 permanent employees. The sampling technique used is purposive sampling, which involves selecting samples based on specific criteria. Based on the research findings and data analysis using SPSS (Statistical Product and Service Solutions), the results indicate that: 1). Work stress has a positive and significant effect on turnover intention. 2). Workload has a positive and significant effect on turnover intention. 3). Work stress and workload together have a positive and significant effect on turnover intention. The implication of these conclusions is that efforts should be made to reduce turnover intention at PT. JNE Padang. Measures that can be taken to lower turnover intention include reducing work stress and workload, thereby decreasing turnover intention.